Coculturing Streptomyces sp. with Acanthamoeba polyphaga enhances the antimicrobial effectiveness of its crude extract against multidrug-resistant Pseudomonas aeruginosa and Escherichia coli - KELI C.C. BARROSO; VERIDIANA G. VIRGINIO; BENI J.M. CHAÚQUE; VINICIUS J. MASCHIO; SUELI T. VAN DER SAND; MARILISE B. ROTT (Anais da Academia Brasileira de Ciências)
Abstract Bacterial infections stand as prominent contributors to global mortality and morbidity rates. Harnessing the potential antimicrobial activity of secondary metabolites derived from natural sources holds promise for developing novel therapeutic drugs. Streptomyces spp. represents pivotal microorganisms in the synthesis of these compounds. Acanthamoeba spp. serves as natural virulence amplifiers for a wide range of bacterial pathogens. This study evaluates the antimicrobial efficacy of crude extracts of Streptomyces sp. cocultured trials with Acanthamoeba polyphaga against multidrug-resistant Pseudomonas aeruginosa and Escherichia coli. The production of crude extracts from Streptomyces sp. was monitored over 28 days. The antimicrobial activity against P. aeruginosa and E. coli was evaluated by measuring the inhibitory halos. Viability amoebae and bacteria were assessed. A slight decrease in the viability of A. polyphaga was noted during the coculture. Conversely, coculture promoted bacterial growth and facilitated the synthesis of extracts that showed antimicrobial effects against P. aeruginosa and E. coli, while showing no impact on amoebae. The extracts were active mainly against P. aeruginosa. The findings show that the interaction between A. polyphaga and Streptomyces sp. modulates the production of antimicrobial secondary metabolites by bacteria. Further investigations are needed to characterize the nature of this modulation, and the bactericidal components.